(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Navoi region is one of the regions that has great tourist potential like other regions, but does not use them to the full. There are ecological, geological, historical, archaeological, architectural, recreational, health, gastronomic and monumental tourist resources in the region. Navoi region is one of the regions that have great tourist potential like other regions, but they are not fully utilized. There are ecological, geological, historical, archaeological, architectural, recreational, health, gastronomic and monumental tourist resources in the region.